LITERATURE REVIEW: PENGARUH PEMBERIAN VITAMIN B TERHADAP PERBAIKAN KLINIS PASIEN DENGAN CARPAL TUNNEL SYNDROME - Adeliana Hardinawati; Pagan Pambudi; Pandji Winata Nurikhwan; Muhammad Welly Dafif; Mohammad Bakhriansyah (Homeostasis, 2022)
Carpal tunnel syndrome (CTS) is an entrapment neuropathy with symptoms such as hand pain, paresthesias in the fingers innervated by the median nerve, weakness, and thenar muscle atrophy. The purpose of this literature review is to analyze the effectiveness of vitamin B administration on clinical improvement in CTS patients. Data were obtained by searching using Google Scholar, PubMed, and Science Direct published from 2011 to 2021. After the article selection process, 7 articles were included in this literature review, of which there were two articles showing that vitamin B6 can improve clinical symptoms of patients with CTS, one article showed that methylcobalamin had an effect on clinical improvement of CTS with and without DM, and 4 articles showed that the combination of vitamins B1, B6, and B12 was effective in reducing the VAS and TSS of subjects with CTS. Vitamin B6, methylcobalamin, and a combination of vitamins B1, B6, and B12 are effective as conservative therapy in improving clinical symptoms in patients with mild to moderate CTS